(untitled) (diségno, 2024)
This contribution highlights how the photography of architectural models was an important tool for representing architecture, often leading to emblematic images of a project. This study also presents a revealing series of artistic experiences in which the architectural model becomes a primary subject of photography. While traditional photography of architectural models often looked for realism that could anticipate the constructed building, this task has, for years now, often been assigned to digital representation. The model is therefore represented photographically in a decidedly more abstract manner, allowing it to enunciate particular aspects of the project. It is interesting to note how still today, important architects are particularly interested in taking photographs of project models, developing important collaborations with photographers. In recent decades, photography and some of its trends have often caused problems for its relationship to reality: by manipulating images, some authors completely detach themselves from any material nature, even producing entirely synthetic images. Instead, through the use of models, one still operates on a material plane, but implements a true artificial reality, and what is real becomes rebuilt through scale models with different degrees of realism or abstraction, presenting a virtual reality expressly conceived by the authors.